Ranger's Apprentice: Halt's Peril - Book 9 - Flanagan, John (John Anthony) (New York : Philomel Books, 2010)
Tennyson, the false prophet of the Outsider cult, has escaped and Halt is determined to stop him before he crosses the border into Araluen, but Genovesan assassins put Will and Halt's extraordinary archery skills to the test.
aOriginally published: Australia : Random House Australia Children's Books, 2009.
Keywords: Cults -- Fiction; Insurgency -- Fiction; Fiction